Effects of Branding on Customer Loyalty in Hotels: A Case Study of Jevine Hotel Kabusu. - Kyarisiima, Pamela (Kabale University., 2024)
The study was about investigating the effects of branding on customer loyalty in hotels. A case study of Jevine Hotel Kabusu. The study was guided by three objectives which were: to find out the factors that contribute to hotel brand loyalty at Jevine Hotel Kabusu, to find out the relationship between branding and customer loyalty, and to identify the practices for hotel managers to improve hotel brand loyalty. A targeted population was 80 respondents who were considered for the study. These included marketing manager, receptionist, waiters, and customers. Both simple random and purposive sampling techniques in identifying the study sample population. The methods that were used in data collection included surveys, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. According to the findings, several respondents agreed that the factors that contribute to hotel brand loyalty at Jevine Hotel Kabusu include awareness, brand recognition, trust and Credibility, image, confidence, trust in Consistency, and Brand Reputation. The study revealed there is a relationship between branding and customer loyalty and these included brand image and perception, consistency in Service and experience, brand Recognition and Trust, Emotional Connection, loyalty Programs and Incentives, and Online Reputation Management. From objective three, the study indicated there is a relationship between branding and customer loyalty and these included brand image and perception, consistency in Service and experience, brand Recognition and Trust, Emotional Connection, loyalty Programs and Incentives, and Online Reputation Management. The study further concluded by showing the factors that contribute to hotel brand loyalty at Jevine Hotel Kabusu including awareness, brand recognition, trust and Credibility, image, confidence, trust in Consistency, and Brand Reputation.